INCLUSIVE DOMOTICS AND THE GENERATIONAL RELAY IN THE FIELD, BY INTELLIGENT SYSTEMS - Damián García, Iván Camilo
An intelligent system is that program that resembles the intelligence of a human being, being a term commonly used for expert systemsor home automation systems. Knowing this, we must understand that home automation is a technique, which through the technology applied in everyday processes is responsible for providing comfort and a better quality of life to its users. In this work we will demonstrate how home automation currently only seems to be affordable for people with high resources and is composed of products that are not viable for the economy of people from Latin America. In this context and bearing in mind that we live in countries where a large part of its population still works in the rural area, it becomes a necessity to use this technology to speed up the pace of life and enter the world’s productive current competition.